CREATIVE INDIVIDUALITY IN THE DESCRIPTION OF A FEMALE IMAGE IN THE WORKS OF KAZUO ISHIGURO - Irsaliyeva Madinakhon Anvarbek qizi; Xidirova Zukhra Po`latovna (Western European Studies, 2024)
English literature is rich in the writers who used women image in essential works. Kazuo Ishiguro is an example among postmodernism writers. The character of the female characters in the novels, their love, memories, determination are described by the writer in a unique way. Image tools used to describe images in each work can show the skill of the writer.
Keywords: Literature; writer; female image